ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE PADA WEBSITE PEMILIHAN RAYA KELUARGA MAHASISWA UPN VETERAN JAKARTA MENGGUNAKAN PENDEKATAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Ezra Paskalis Refanus (2021)
The General Election of the Student or Pemira is a routine activity carried out by active students at UPN Veteran Jakarta. Pemira activities are carried out to elect candidates for chairman, deputy, and student organization administrators, both at the faculty level and university level. Pemira at UPN Veteran Jakarta is carried out in a democratic manner, which is through general elections. At first, the election was held directly in each faculty. However, as time goes by and the demands of the situation, Pemira is carried out online through a website specifically designed to collect voters' votes. The high level of traffic during simultaneous elections, coupled with many parties who wish to change the vote count illegally, as well as the use that is considered too complicated, made students become pessimistic about the online election system implemented by the committee. This study aims to improve the utility of the Pemira MPM UPN Veteran Jakarta's website by using the User Experience Questionnaire (UEQ) approach. After being analyzed using the UEQ method, a redesign of the display that is more attractive to students can be carried out. It is hoped that this research can form a redesigned Pemira website that is user-friendly and increases student participation in the General Election of the Student.